Chloroprene polymer latex, its manufacturing method, and water-based adhesive using said chloroprene polymer latex

By optimizing the gel content, molecular weight, and emulsifier composition of chloroprene polymer latex, the adhesive strength of aqueous adhesives is significantly improved, addressing the limitations of existing technologies in achieving high initial adhesion in wet conditions.

JP7659573B2Active Publication Date: 2025-04-09DENKA CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022563725
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-19
Filing Date
2021-11-12
Publication Date
2025-04-09
Estimated Expiration
2041-11-12

AI Technical Summary

Technical Problem

Existing aqueous adhesives based on chloroprene polymer latex have lower adhesive strength compared to solvent-based adhesives, particularly in the wet state, and face challenges in achieving high initial adhesion strength.

Method used

A chloroprene polymer latex with a specific gel content and weight average molecular weight, combined with emulsifiers like rosin acid or its alkali metal salts, and adjusted pH, is used to enhance the initial adhesion strength, especially in the wet state.

Benefits of technology

The described chloroprene polymer latex achieves excellent initial adhesion strength, particularly in the wet state, making it suitable for applications requiring high bonding performance, such as bonding polyurethane foams.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659573000001
    Figure 0007659573000001
Patent Text Reader

Abstract

A chloroprene polymer latex suitable for use in an aqueous adhesive and which constitutes an aqueous adhesive that has excellent initial bonding strength and that in particular has excellent bonding strength in a moist state. This chloroprene polymer latex contains a chloroprene polymer and one or more emulsifiers selected from rosin acid and an alkali metal salt thereof, and is characterized in that the toluene-insoluble gel content ratio in the solid content of the chloroprene polymer latex is less than or equal to 20 mass%, and the weight average molecular weight of the toluene-soluble sol content in the solid content of the chloroprene polymer latex is greater than or equal to 1 million.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chloroprene polymer latex that is effective as an adhesive, a method for producing the same, and an aqueous adhesive using the chloroprene polymer latex. More specifically, the present invention relates to a chloroprene polymer latex that is excellent in initial adhesive strength, particularly adhesive strength in a wet state, a method for producing the same, and an aqueous adhesive using the chloroprene polymer latex. [Background technology]

[0002] Chloroprene polymers are suitable for use in adhesive applications such as solvent-based contact adhesives and graft adhesives because they can provide high adhesive strength at low pressure to a wide range of adherends. However, solvent-based adhesives have the risk of ignition in the work environment, the cost of special exhaust and recovery equipment required to prevent this, and volatile organic compound (VOC) and solvent regulations are becoming stricter every year due to concerns about environmental pollution and human health. In order to comply with these regulations, water-based adhesives using chloroprene polymer latexes have been actively developed to eliminate solvents, but water-based adhesives have the problem of having lower adhesive strength than conventional solvent-based adhesives.

[0003] Thus, two-component adhesives have been investigated as one technique for improving the adhesive strength, particularly the initial adhesive strength, of adhesives. For example, two-component adhesives are known that use a composition in which a specific chloroprene polymer latex composition is mixed with specific amounts of an acrylic latex or SBR latex and an anionic surfactant as the base agent, and that use a polyvalent metal salt as the curing agent (see Patent Documents 1 and 2), and these are used by adjusting the balance between pot life and initial adhesion.

[0004] Japanese Patent Laid-Open Publication No. 2007-332207 (see Patent Document 3) discloses an aqueous adhesive containing a chloroprene polymer latex composition, a polyoxyalkylene alkyl ether sulfate, and a pH adjuster. WO 2016 / 133190 and WO 2016 / 133191 (see Patent Documents 4 and 5) disclose one-component water-based adhesives comprising a blend of a chloroprene homopolymer latex and a chloroprene copolymer latex containing a chloroprene copolymer, or an acrylic polymer latex containing an acrylic polymer. Moreover, WO 2008 / 026671 (see Patent Document 6) discloses an aqueous adhesive characterized by containing a specific acid acceptor and a specific antioxidant in a specific chloroprene polymer latex composition. The aqueous adhesives prepared according to the examples in these publications exhibit adhesive strength by being applied, dried, and then bonded together. However, the initial adhesive strength, particularly the adhesive performance in a wet state, is not sufficient, and improvement of this has been an issue. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 56-59874 [Patent Document 2] Japanese Patent Application Publication No. 9-188860 [Patent Document 3] JP 2007-332207 A [Patent Document 4] International Publication No. 2016 / 133190 [Patent Document 5] International Publication No. 2016 / 133191 [Patent Document 6] International Publication No. 2008 / 026671 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a chloroprene polymer latex suitable for use in aqueous adhesives, which gives an aqueous adhesive having excellent initial adhesive strength, particularly excellent adhesive strength in a wet state, and to provide an aqueous adhesive using the same. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive studies to find that the above-mentioned problems can be solved by using a chloroprene polymer latex having a solid content containing a specific amount of gel and a weight average molecular weight of a sol content of the solid content falling within a specific numerical range.

[0008] That is, the present invention relates to a chloroprene polymer latex comprising one or more emulsifiers selected from rosin acid or an alkali metal salt thereof, and a chloroprene polymer, wherein the content of a gel fraction which is a toluene-insoluble fraction in the solid fraction of the chloroprene polymer latex is 20 mass% or less, and the weight average molecular weight of a sol fraction which is a toluene-soluble fraction in the solid fraction of the chloroprene polymer latex is 1,000,000 or more.

[0009] Preferably, the chloroprene polymer latex is characterized in that the amount of 1 / 3 mol / L hydrochloric acid required to be dropped to adjust the pH to 10.5 is 0.1 to 10.0 parts by mass based on 100 parts by mass of the chloroprene polymer latex.

[0010] In accordance with another aspect of the present invention, there is provided a water-based adhesive comprising the above-described chloroprene polymer latex. Preferably, the aqueous adhesive contains 1 to 20 parts by mass of an amino acid based on 100 parts by mass of the chloroprene polymer latex. Preferably, the aqueous adhesive contains 0.1 to 30 parts by mass of a plasticizer based on 100 parts by mass of the chloroprene polymer latex. Preferably, the water-based adhesive is 20mm thick x 50mm long x 50mm wide and has a density of 30kg / m 3 Apply 70g / m2 of adhesive to the urethane foam surface. 2After an open time of 10 seconds, the urethane foam pieces were bonded together, and the combined thickness of the bonded urethane foam pieces (40 mm) was compressed to 10 mm and held for 5 seconds. The pieces were then released and left for 10 seconds. A tensile test was then carried out in the direction perpendicular to the bonded surface. The initial adhesive strength was 5.5 N / cm 2 That's all. Preferably, the adherend is a foam.

[0011] According to still another aspect of the present invention, there is provided a method for producing the chloroprene polymer latex, comprising adding 0.005 to 0.1 part by mass of a chain transfer agent based on 100 parts by mass in total of a chloroprene monomer and a monomer copolymerizable with the chloroprene monomer, and polymerizing the chloroprene monomer at a temperature lower than 20° C. until a polymerization conversion rate of the chloroprene monomer reaches 50 to 90%. Effect of the Invention

[0012] The chloroprene polymer latex of the present invention maintains the inherent high crystallization rate of chloroprene polymers and has improved initial adhesive strength, particularly in a wet state, and can therefore be widely used as an adhesive suitable for applications requiring excellent initial adhesive strength, particularly as a spray-type adhesive for use in bonding polyurethane foams. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below.

[0014] 1. Chloroprene polymer latex The chloroprene polymer latex according to one embodiment of the present invention contains one or more emulsifiers selected from rosin acid or an alkali metal salt thereof, and a chloroprene polymer. The chloroprene polymer latex according to one embodiment of the present invention can be obtained by emulsion polymerization of a chloroprene monomer, or a monomer copolymerizable with the chloroprene monomer and a chloroprene monomer in the presence of an emulsifier, and contains one or more emulsifiers selected from rosin acid or an alkali metal salt thereof, and a chloroprene polymer as main components, and may contain a solvent such as water, and may contain other additives used during emulsion polymerization. The chloroprene polymer latex according to one embodiment of the present invention can contain, when the solid content is 100% by mass, the total of one or more emulsifiers selected from rosin acid or an alkali metal salt thereof and the chloroprene polymer is 90% by mass or more, preferably 92% by mass or more, more preferably 95% by mass or more, and more preferably 98% by mass or more.

[0015] The chloroprene polymer according to one embodiment of the present invention can be obtained by emulsion polymerization of a chloroprene monomer, or a chloroprene monomer and a monomer copolymerizable with the chloroprene monomer in the presence of an emulsifier. The chloroprene polymer in the present invention is a homopolymer of 2-chloro-1,3-butadiene (hereinafter referred to as a chloroprene monomer) or a copolymer of a chloroprene monomer and another monomer copolymerizable with the chloroprene monomer, and examples of the other monomer include 1-chloro-1,3-butadiene, 2,3-dichloro-1,3-butadiene, butadiene, isoprene, styrene, acrylonitrile, sulfur, acrylic acid and its esters, and methacrylic acid and its esters. Two or more of these may be used in combination as the other monomer.

[0016] When the chloroprene polymer is a copolymer of a chloroprene monomer and another monomer copolymerizable with the chloroprene monomer, the chloroprene polymer preferably contains 50 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more of structural units derived from the chloroprene monomer when the entire chloroprene polymer is taken as 100 parts by mass. The chloroprene polymer may also be a homopolymer of the chloroprene monomer.

[0017] In the chloroprene polymer latex according to one embodiment of the present invention, when the solid content of the entire chloroprene polymer latex is taken as 100 mass%, the gel content in the solid content is 20 mass% or less, and the weight average molecular weight of the sol content in the solid content is 1,000,000 or more.

[0018] In the present invention, the gel content of the solid content of the chloroprene polymer latex refers to a component insoluble in toluene solvent among the solid content of the chloroprene polymer latex, and the sol content refers to a component soluble in toluene solvent among the solid content of the chloroprene polymer latex. The gel content can be calculated as follows. First, chloroprene polymer latex is freeze-dried and then precisely weighed to obtain A (g). This is dissolved in toluene (adjusted to 0.6%) at 23°C for 20 hours, and the gel is separated using a centrifuge and then a 200-mesh wire screen. The gel content is air-dried, then dried in an atmosphere at 110°C for 1 hour, precisely weighed, and obtained as B. The gel content can be calculated according to the following formula. Gel content = B / A x 100 (%) The weight average molecular weight of the sol fraction can be determined by carrying out a GPC measurement on the sol fraction obtained by the above separation. Here, the molecular weight can be determined in terms of polystyrene.

[0019] The excellent initial adhesive strength in the present invention is due to the chloroprene polymer latex containing a large amount of sol content with excellent molecular mobility. Therefore, fusion of chloroprene polymer molecular chains at the adhesive interface occurs quickly, adhesive strength is instantaneously developed, and excellent initial adhesive strength can be developed. If the gel content of the chloroprene polymer latex exceeds 20% by mass, the initial adhesive strength decreases, which is not preferable. The gel content of the solid content of the chloroprene polymer latex in the present invention is 20% by mass or less. More preferably, it is 10% by mass or less. The gel content of the solid content of the chloroprene polymer latex can be, for example, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, or 0% by mass, and may be within a range between any two of the numerical values ​​exemplified here. The chloroprene polymer latex may also be one that does not contain gel content.

[0020] In the present invention, the weight average molecular weight of the sol content, i.e., the toluene solvent soluble component of the solid content of the chloroprene polymer latex, plays an important role, and the weight average molecular weight of the sol of the solid content of the chloroprene polymer latex in the present invention is 1 million or more. When the weight average molecular weight of the sol content is 1 million or more, entanglement of the molecular chains of the chloroprene polymer is easily caused, and the adhesive strength is improved. In addition, from the viewpoint of productivity, it is preferable that the weight average molecular weight of the sol content is 2.5 million or less. From the viewpoint of adhesive properties and productivity, the weight average molecular weight of the sol content is more preferably in the range of more than 1.1 million and 2.5 million or less, preferably 1.2 million or more and 2 million or less, and even more preferably more than 1.25 million and 2 million or less. The weight average molecular weight of the sol is, for example, 1,000,000, 1,050,000, 1,100,000, 1,150,000, 1,200,000, 1,250,000, 1,300,000, 1,350,000, 1,400,000, 1,450,000, 1,500,000, 1,600,000, 1,700,000, 1,800,000, 1,900,000, 2,000,000, 2,100,000, 2,200,000, 2,300,000, 2,400,000, or 2,500,000, and may be within a range between any two of the numerical values ​​exemplified here.

[0021] The chloroprene polymer latex according to one embodiment of the present invention contains one or more emulsifiers selected from rosin acid or an alkali metal salt thereof. That is, in one embodiment of the present invention, the emulsifier used in emulsion polymerization is preferably one or more selected from rosin acid or an alkali metal salt thereof. When rosin acid or an alkali metal salt thereof is used as the emulsifier, the emulsion stability of the chloroprene polymer latex composition is easily reduced when mechanical stimulation is applied to the chloroprene polymer latex composition. Therefore, when the chloroprene polymer latex composition is used as an adhesive, excellent initial adhesive strength can be exhibited.

[0022] The most preferred emulsifier used in emulsion polymerization is rosin acid, and any of wood rosin acid, gum rosin acid, tall oil rosin acid, disproportionated rosin acid obtained by disproportionating these acids, and alkali metal salts thereof can be used as the rosin acid, and it is particularly preferred to use disproportionated rosin acid. The chloroprene polymer latex according to one embodiment of the present invention may contain two or more kinds of rosin acid or alkali metal salts thereof. The chloroprene polymer latex according to one embodiment of the present invention contains preferably 1.0 to 4.5 mass % of rosin acid or an alkali metal salt thereof, more preferably 1.5 to 4.0 mass %, and further preferably 2.0 to 3.5 mass %, in the chloroprene polymer latex, when the chloroprene polymer latex is taken as 100 mass %.

[0023] The chloroprene polymer latex according to one embodiment of the present invention may further contain, in addition to the rosin acid or an alkali metal salt thereof, an anionic emulsifier or dispersant such as an alkylsulfonate having 8 to 20 carbon atoms, an alkylaryl sulfate, a condensate of sodium naphthalenesulfonate and formaldehyde, or sodium alkyldiphenyletherdisulfonate. The chloroprene polymer latex according to one embodiment of the present invention may contain, in addition to the rosin acid or an alkali metal salt thereof, 0.05 to 5 parts by mass, preferably 0.1 to 2 parts by mass of an anionic emulsifier or dispersant in the chloroprene polymer latex when the chloroprene polymer latex is taken as 100 parts by mass.

[0024] The emulsifier may be used in combination with a nonionic emulsifier or dispersant. By using a nonionic emulsifier in combination, the low temperature stability of the chloroprene polymer latex composition and the adhesive properties when used as an adhesive can be improved. The chloroprene polymer latex according to one embodiment of the present invention may further contain such a nonionic emulsifier or dispersant.

[0025] The chloroprene polymer latex according to one embodiment of the present invention preferably contains an alkali metal salt from the viewpoint of polymerization control and initial adhesive strength, particularly adhesive performance in a wet state. Examples of the alkali metal salt include potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium hydrogen carbonate, and sodium hydrogen carbonate. Sodium hydroxide and potassium hydroxide are preferred from the viewpoints of cost, water solubility, and the like. Two or more of these metal alkali salts may be used in combination.

[0026] In the chloroprene polymer latex according to one embodiment of the present invention, the amount of 1 / 3 mol / L hydrochloric acid required to adjust the pH to 10.5 is preferably 0.1 to 10.0 parts by mass relative to 100 parts by mass of the chloroprene polymer latex. In the present invention, if the amount of 1 / 3 mol / L hydrochloric acid required to adjust the pH to 10.5 is 0.1 or less, the storage stability of the chloroprene polymer latex decreases, and if it is 10.0 or more, the polymerization controllability and productivity of the chloroprene polymer decrease. From the viewpoint of adhesion performance, storage stability, etc., it is more preferable that the amount of 1 / 3 mol / L hydrochloric acid required to adjust the pH to 10.5 is 0.5 to 8.0 parts by mass. The amount of 1 / 3 mol / L hydrochloric acid required to adjust the pH to 10.5 can be controlled by adjusting the amount of alkali metal salt contained in the chloroprene polymer latex.

[0027] The chloroprene polymer latex according to one embodiment of the present invention preferably has a solid content concentration of 40 to 60% by mass, and may be, for example, 40, 45, 50, 55, or 60% by mass, and may be within a range between any two of the numerical values ​​exemplified here. The solid content concentration can be expressed as D / C×100(%), where Cg is the chloroprene polymer latex and Dg is the mass after drying it for 1 hour under a 125° C. atmosphere. When the solid content concentration of the chloroprene polymer latex is within the above numerical range, when the chloroprene polymer is used to prepare an adhesive, drying can be performed sufficiently quickly and a uniform adhesive layer can be formed.

[0028] 2. Method for producing chloroprene polymer latex The chloroprene polymer latex according to one embodiment of the present invention can be obtained by a production method including a step of emulsion polymerizing a chloroprene monomer, or a monomer copolymerizable with the chloroprene monomer, and the chloroprene monomer in the presence of an emulsifier.

[0029] The types and amounts of the chloroprene polymer to be polymerized and the monomer copolymerizable with the chloroprene monomer are as described above.

[0030] In the method for producing a chloroprene polymer latex according to one embodiment of the present invention, it is preferable to use one or more emulsifiers selected from rosin acid or an alkali metal salt thereof during emulsion polymerization. The amount of the one or more emulsifiers selected from rosin acid or an alkali metal salt thereof is preferably 0.5 to 10 parts by mass, more preferably 2 to 6 parts by mass, based on 100 parts by mass of the total of the chloroprene polymer to be polymerized and the monomer copolymerizable with the chloroprene monomer.

[0031] In the method for producing a chloroprene polymer latex according to one embodiment of the present invention, in addition to rosin acid or an alkali metal salt thereof, an anionic emulsifier or dispersant such as an alkylsulfonate having 8 to 20 carbon atoms, an alkylaryl sulfate, a condensate of sodium naphthalenesulfonate and formaldehyde, or sodium alkyldiphenyletherdisulfonate may be used in combination during emulsion polymerization. When an anionic emulsifier or dispersant is used in combination in addition to rosin acid or an alkali metal salt thereof, the amount of the anionic emulsifier or dispersant added may be 0.05 to 5 parts by mass, and preferably 0.1 to 2 parts by mass, per 100 parts by mass of the total of the chloroprene polymer to be polymerized and the monomer copolymerizable with the chloroprene monomer.

[0032] In the method for producing a chloroprene polymer latex according to one embodiment of the present invention, it is preferable to add an alkali metal salt during emulsion polymerization. Examples of the alkali metal salt include potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium hydrogen carbonate, and sodium hydrogen carbonate. The amount of the alkali metal salt added is preferably such that the amount of 1 / 3 mol / L hydrochloric acid dropped to adjust the pH of the finally obtained chloroprene polymer latex to 10.5 is 0.1 to 10.0 parts by mass, more preferably 0.5 to 8.0 parts by mass, based on 100 parts by mass of the chloroprene polymer latex. The amount of the alkali metal salt added during emulsion polymerization is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the total of the chloroprene polymer to be polymerized and the monomer copolymerizable with the chloroprene monomer.

[0033] During emulsion polymerization of chloroprene monomers, etc., it is preferable to add a chain transfer agent to adjust the molecular weight and molecular weight distribution of the chloroprene polymer. The chain transfer agent may also be added during polymerization. As the chain transfer agent, long-chain alkyl mercaptans such as n-dodecyl mercaptan and t-dodecyl mercaptan, and dialkyl xanthogen disulfides such as diisopropyl xanthogen disulfide and diethyl xanthogen disulfide are preferable. From the viewpoint of easy control of the molecular weight and gel content, long-chain alkyl mercaptans are more preferable. Two or more of these chain transfer agents may be used in combination. The total amount of the chain transfer agent added during emulsion polymerization is preferably 0.005 to 0.1 parts by mass relative to 100 parts by mass of the total of the chloroprene polymer to be polymerized and the monomer copolymerizable with the chloroprene monomer, and can be, for example, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here.

[0034] The polymerization conversion rate of the chloroprene monomer during emulsion polymerization of the chloroprene polymer is preferably 50% by mass or more and less than 90% by mass, more preferably 60 to 85% by mass, and may be, for example, 50, 55, 60, 65, 70, 75, 80, 85, or 90% by mass, and may be within a range between any two of the numerical values ​​exemplified here. When the polymerization conversion rate of the chloroprene monomer is less than 50%, the solid content concentration of the chloroprene polymer latex decreases, which not only places a burden on the drying process after application of the adhesive and makes it difficult to uniformize the adhesive layer, but also causes problems such as odor due to the residual chloroprene monomer, and deterioration of the tackiness and adhesive strength. When the polymerization conversion rate is 90% by mass or more, the branching in the chloroprene polymer may increase, or the molecular weight distribution may widen due to the increase in molecular weight, which may cause a problem of deterioration of the initial adhesive strength, which is an important performance in the present invention. The polymerization conversion rate (mass%) is calculated by [(polymer mass / monomer mass sum)×100]. Hereinafter, the polymerization conversion rate may be simply referred to as the polymerization rate.

[0035] Chloroprene polymers can be polymerized in the range of 0 to 45°C, but are preferably polymerized at a low temperature of 5 to 15°C. For example, they can be polymerized at 0, 5, 10, 15, 20, 25, 30, 35, 40, or 45°C, and may be within the range between any two of the values ​​exemplified here. It is known that chloroprene homopolymers contain trans-1,4-bonds at 85% or more, and their molecular structure is relatively regular. Chloroprene homopolymers have the properties of a typical crystalline polymer due to the high regularity of this molecular structure. By setting the polymerization temperature at a low temperature of 5 to 15°C, the ratio of trans-1,4-bonds in the polychloroprene molecule is further increased, so that a chloroprene homopolymer with a higher crystallization rate can be obtained, and when this is used as a one-component water-based adhesive, sufficient adhesive strength is achieved.

[0036] As the initiator for emulsion polymerization, a conventional radical polymerization initiator can be used, specifically, an organic or inorganic peroxide such as benzoyl peroxide, potassium persulfate, ammonium persulfate, etc., or an azo compound such as azobisisobutyronitrile, etc. A cocatalyst such as anthraquinone sulfonate, potassium sulfite, sodium sulfite, etc. may be used in combination as appropriate.

[0037] In the production of chloroprene polymers, a polymerization terminator is added to terminate the reaction when a predetermined polymerization rate is reached in order to obtain a polymer with the desired molecular weight and distribution. Examples of polymerization terminators include phenothiazine, pt-butylcatechol, hydroquinone, hydroquinone monomethyl ether, and diethylhydroxylamine.

[0038] As described above, the solid content concentration of the chloroprene polymer latex is not particularly limited, but is usually 40 to 65 mass %. The solid content concentration of the chloroprene polymer latex can be controlled, for example, by adjusting the blending ratio including a solvent such as water during emulsion polymerization of the chloroprene polymer, or by evaporating the water contained in the chloroprene polymer latex under reduced pressure.

[0039] 3. Water-based adhesives The chloroprene polymer latex according to one embodiment of the present invention may be a chloroprene polymer latex composition containing the chloroprene polymer latex, and in particular, may be a water-based adhesive.

[0040] The aqueous adhesive according to one embodiment of the present invention may contain a pH adjuster. The pH adjuster is blended to improve the initial adhesive strength and storage stability when the chloroprene polymer latex composition is used as an aqueous adhesive. As the pH adjuster, a weak acid or a buffer solution can be used, and specifically, at least one compound selected from hydroxy acids such as citric acid and glycolic acid, boric acid, and amino acids is preferable, and among these, amino acids are more preferable. Specific examples of the amino acids include glycine, alanine, threonine, and proline. The use of glycine, which is a type of amino acid, is more preferable in terms of cost, adhesive performance, ease of handling, and the like.

[0041] The amount of pH adjuster added is not particularly limited, but it is preferable to use an amount that can adjust the pH of the aqueous adhesive to a range of 7 to 10. More preferably, it is desirable to add an amount that can adjust the pH to a range of 8 to 10.

[0042] When an amino acid, particularly glycine, is used as a pH adjuster, the amount of the amino acid is preferably 1 to 20 parts by mass, more preferably 2 to 16 parts by mass, and even more preferably 3 to 13 parts by mass, per 100 parts by mass of the chloroprene polymer latex, so that sufficient adhesive strength can be expressed at advantageous cost.

[0043] The aqueous adhesive according to one embodiment of the present invention may contain a plasticizer. The amount of the plasticizer added is 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 2 to 15 parts by mass, relative to 100 parts by mass of the chloroprene polymer latex. By adding a plasticizer, the initial strength of the aqueous adhesive containing the obtained chloroprene polymer latex can be improved, and the texture of the adhesive film after drying can be softened. In particular, when using as an adhesive for polyurethane foam, it is preferable to add a plasticizer. The plasticizer is preferably one that has good compatibility with the chloroprene polymer, and is not particularly limited, but examples thereof include dibutyl sebacate, dibutyl phthalate, dioctyl adipate, dioctyl azelate, dioctyl sebacate, dioctyl phthalate, tricresyl phosphate, and cresyl diphenyl phosphate.

[0044] Chloroprene polymer latex compositions are generally susceptible to deterioration due to oxygen. In the present invention, a stabilizer such as an antioxidant can be appropriately used in the water-based adhesive as long as it does not impair the effects of the invention.

[0045] When an oxidizing agent is blended in a chloroprene polymer latex composition, particularly in an aqueous adhesive, the amount of antioxidant added is preferably 0.1 to 3 parts by mass per 100 parts by mass of the solid content of the chloroprene polymer latex. By setting the amount within this range, the stability of flexibility over time of the resulting adhesive layer can be improved. When the antioxidant is insoluble in water or destabilizes the emulsified state of the chloroprene polymer latex composition, it is preferable to prepare the antioxidant in advance as an aqueous dispersion and then add it.

[0046] In the chloroprene polymer latex composition of the present invention, particularly in the water-based adhesive, additives other than those mentioned above, such as fillers, tackifiers, pigments, colorants, wetting agents, defoamers, thickeners, etc., can be appropriately used within the scope of not impairing the effects of the present invention. In addition, other resin emulsions (latexes) may be supplementarily blended up to an upper limit of 30 mass% (solid content equivalent) of the total composition. Specific examples include resin emulsions such as (modified) vinyl acetate, vinyl acetate-acrylic mixtures, acrylic-styrene mixtures, and urethane.

[0047] The water-based adhesive according to one embodiment of the present invention is 20 mm thick x 50 mm long x 50 mm wide and has a density of 30 kg / m 3 Apply 70g / m2 of adhesive to the urethane foam surface. 2 After an open time of 10 seconds, the urethane foam pieces were bonded together, and the combined thickness of the bonded urethane foam pieces (40 mm) was compressed to 10 mm and held for 5 seconds. The pieces were then released and left for 10 seconds. A tensile test was then carried out in the direction perpendicular to the bonded surface. The initial adhesive strength was 5.5 N / cm 2 It is preferable that the resistance is 6.0N / cm or more. 2 More preferably, it is 6.5N / cm or more. 2 It is even more preferable that the above is satisfied. Conventionally, there has been a demand for aqueous adhesives that have high adhesive strength even when the open time is long and also when the open time is short, but with existing technology, it has not been possible to obtain high adhesive strength with a short open time, such as an open time of 10 seconds. With the aqueous adhesive according to one embodiment of the present invention, high adhesive strength can be obtained even with an open time of 10 seconds.

[0048] The water-based adhesive according to one embodiment of the present invention is 20 mm thick x 50 mm long x 50 mm wide and has a density of 30 kg / m 3 Apply 70g / m2 of adhesive to the urethane foam surface. 2After an open time of 1 minute, the urethane foam pieces were bonded together, and the combined thickness of the bonded urethane foam pieces (40 mm) was compressed to 10 mm and held for 5 seconds. The pieces were then released and left for 10 seconds. A tensile test was then carried out in the direction perpendicular to the bonded surface. The initial adhesive strength was 6.0 N / cm. 2 It is preferable that the resistance is 6.5N / cm or more. 2 More preferably, it is 7.0N / cm or more. 2 The water-based adhesive according to one embodiment of the present invention can provide high adhesive strength whether the open time is 10 seconds or 1 minute, and can therefore provide the advantage of allowing for variation in open time at work sites where water-based adhesives are used, thereby increasing the degree of freedom in the process.

[0049] The aqueous adhesive according to one embodiment of the present invention may be a one-liquid aqueous adhesive. Suitable adherends for the aqueous adhesive according to one embodiment of the present invention are foams made of materials such as polyurethane, ethylene-vinyl acetate copolymer, and polyethylene, or water-absorbent adherends such as wood, cloth, and textiles.

[0050] The chloroprene polymer latex composition containing the chloroprene polymer latex produced under the above-mentioned various conditions has excellent initial adhesive strength, contact property, water resistance, spray coating property and storage stability, and can be suitably used as an aqueous adhesive, particularly a one-component aqueous adhesive. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples. Note that these are merely illustrative and do not limit the scope of the present invention.

[0052] [Example 1] Using a reactor with an internal volume of 10 liters, 90 parts by mass of water, 4.5 parts by mass of disproportionated rosin acid, 0.5 parts by mass of potassium hydroxide, and 0.3 parts by mass of sodium salt of formaldehyde naphthalene sulfonic acid condensate were charged under a nitrogen stream, and after dissolving, 100 parts by mass of chloroprene monomer and 0.05 parts by mass of n-dodecyl mercaptan were added while stirring. Potassium persulfate was used as an initiator, and polymerization was carried out at 10°C under a nitrogen atmosphere, and when the polymerization rate reached 70%, an emulsion of phenothiazine was added to terminate the polymerization. Unreacted chloroprene monomer was removed under reduced pressure to obtain a chloroprene polymer latex. Furthermore, water was evaporated under reduced pressure to perform concentration, and the solid content concentration was adjusted to 55% by mass. The amount of 1 / 3 mol / L hydrochloric acid dropped to adjust the pH to 10.5 was 7.6 parts by mass for 100 parts by mass of the obtained chloroprene polymer latex.

[0053] The gel content of the solid content of the obtained chloroprene polymer latex and the weight average molecular weight of the sol content were measured according to the following methods. [Gel content] The chloroprene polymer latex sample was freeze-dried and precisely weighed to obtain A. It was dissolved in toluene (adjusted to 0.6%) at 23°C for 20 hours, centrifuged, and the gel was separated using a 200-mesh wire screen. The gel fraction was air-dried, then dried in an atmosphere at 110°C for 1 hour, precisely weighed, and obtained B. The gel fraction was calculated according to the following formula. Gel content = B / A x 100 (%)

[0054] [Weight average molecular weight of sol content] GPC measurements were performed under the following conditions. Weight average molecular weight was calculated based on polystyrene equivalent. The sample was prepared by dissolving the separated sol in 0.1% THF solution. Measurement of number average molecular weight (Mn), weight average molecular weight (Mw), molecular weight distribution (Mw / Mn) and block copolymer formation rate by gel permeation chromatography (GPC) Apparatus: Tosoh gel permeation chromatograph (HLC-8320) Column: Tosoh TSKgel ALPHA-M Eluent: Tetrahydrofuran (Kanto Chemical) Eluent flow rate: 1.0ml / min Column temperature: 40℃ Detection method: Differential refractive index (RI) meter Calibration curve: Created using standard polystyrene

[0055] 100 parts by mass of the chloroprene polymer latex obtained above was mixed with 5 parts by mass of dibutyl sebacate and 6 parts by mass of glycine using a Three-One Motor to prepare an aqueous adhesive.

[0056] [Initial adhesive strength 1] Density 30kg / m 3 A polyurethane foam (20 mm thick x 50 mm long x 50 mm wide) was used as the adherend, and a water-based adhesive was applied at 70 g / m2 in an atmosphere of 23°C. 2 After application, the adhesive was left in an atmosphere of 23°C for 10 seconds (open time; OT = 10 seconds), and the adhesive surfaces of two pieces of urethane foam were placed together while the water-based adhesive was still wet, and the adhesive surfaces were compressed from a thickness of 40 mm to 10 mm and held for 5 seconds. After that, the adhesive was left for 10 seconds without pressure (set time; ST = 10 seconds), and immediately a tensile test was performed in the direction perpendicular to the adhesive surface using a tensile tester (A&D Tensilon; tensile speed 200 mm / min) to measure the initial adhesive strength 1.

[0057] [Initial adhesive strength 2] Density 30kg / m 3 A polyurethane foam (20 mm thick x 50 mm long x 50 mm wide) was used as the adherend, and a water-based adhesive was applied at 70 g / m2 in an atmosphere of 23°C. 2 After application, the adhesive was left in a 23°C atmosphere for 1 minute (OT = 1 minute), and while the water-based adhesive was still wet, the adhesive surfaces of two pieces of urethane foam were placed together, compressed from a thickness of 40 mm to 10 mm, and held for 5 seconds. After that, the adhesive was left for 10 seconds without pressure (ST = 10 seconds), and immediately a tensile test was performed in the direction perpendicular to the adhesive surface using a tensile tester (A&D Tensilon; tensile speed 200 mm / min) to measure the initial adhesive strength 2.

[0058] [Examples 2 to 6] The tests were carried out in the same manner as in Example 1, except that the amount of n-dodecyl mercaptan used in the test and the polymerization rate were changed. These were named Examples 2 to 6, and the results of the adhesion tests are summarized in Table 1.

[0059] [Comparative Examples 1 to 4] The tests were carried out in the same manner as in Example 1, except that the amount of n-dodecyl mercaptan used in the test and the polymerization rate were changed. Comparative Examples 1 to 4 were prepared, and the results of the adhesion tests are shown in Table 1.

[0060] [Table 1]

Claims

1. A chloroprene polymer latex comprising one or more emulsifiers selected from a rosin acid or an alkali metal salt thereof and a chloroprene polymer, The content of gel fraction, which is a toluene-insoluble fraction, in the solid content of the chloroprene polymer latex is 20 mass% or less; and the weight average molecular weight of the sol component, which is a toluene-soluble component in the solid component of the chloroprene polymer latex, is 1,250,000 or more; When the aqueous adhesive contains 1 to 20 parts by mass of an amino acid and 0.1 to 30 parts by mass of a plasticizer relative to 100 parts by mass of the chloroprene polymer latex, Thickness 20mm x length 50mm x width 50mm, density 30kg / m 3 The adhesive was applied at 70 g / m 2 After an open time of 10 seconds, the urethane foams were bonded together, and the combined thickness of the bonded urethane foams (40 mm) was compressed to 10 mm and held for 5 seconds. The foams were then released and left for 10 seconds. A tensile test was then performed in the direction perpendicular to the bonded surface. The initial adhesive strength was 5.5 N / cm 2 The chloroprene polymer latex is characterized by the above.

2. 2. The chloroprene polymer latex according to claim 1, wherein the amount of 1 / 3 mol / L hydrochloric acid required to adjust the pH to 10.5 is 0.1 to 10.0 parts by mass based on 100 parts by mass of the chloroprene polymer latex.

3. 3. A water-based adhesive comprising the chloroprene polymer latex of claim 1 or 2.

4. The aqueous adhesive according to claim 3, comprising 1 to 20 parts by mass of an amino acid per 100 parts by mass of the chloroprene polymer latex.

5. 5. The aqueous adhesive according to claim 3, further comprising 0.1 to 30 parts by mass of a plasticizer relative to 100 parts by mass of the chloroprene polymer latex.

6. Thickness 20mm x length 50mm x width 50mm, density 30kg / m 3 The adhesive was applied at 70 g / m 2 After an open time of 10 seconds, the urethane foams were bonded together, and the combined thickness of the bonded urethane foams (40 mm) was compressed to 10 mm and held for 5 seconds. The foams were then released and left for 10 seconds. A tensile test was then performed in the direction perpendicular to the bonded surface. The initial adhesive strength was 5.5 N / cm 2 The aqueous adhesive according to any one of claims 3 to 5.

7. The aqueous adhesive according to any one of claims 3 to 6, wherein the adherend is a foam.

8. 3. The method for producing a chloroprene polymer latex according to claim 1 or 2, wherein 0.005 to 0.1 parts by mass of a chain transfer agent is added to 100 parts by mass of the total of the chloroprene monomer and the monomer copolymerizable with the chloroprene monomer, and polymerization is carried out at a temperature lower than 20° C. until a polymerization conversion rate of the chloroprene monomer reaches 50 to 90%.

Citation Information

Patent Citations

  • Twoopack adhesive

    JP1981059874A

  • Latex for adhesive and chloroprene-based adhesive composition using the sam

    JP1996027448A

  • Adhesive composition

    JP1997188860A

  • Chloroprene latex composition and its production

    JP2000319452A

  • Adhesive composition using chloroprene latex

    JP2001019923A